Design and control of a bidirectional interlinking converter for grid energy storage - Lim, Jing Chuan (Nanyang Technological University, 2022)
Due to the recent climate change summit, Renewable Energy Sources (RES) have been in the spotlight for its greener and more sustainable advantage as compared to its traditional counterpart such as burning of fossil fuel and natural gas. However, RES such as Photovoltaic system (PV system) and Wind Energy Conversion system (WECS) does come with its own set downside. In PV system, the Solar irradiance is greatly influenced by the weather and the time of the day which in turn affect efficiency of the system. In WECS, the wind speed change can greatly affect the voltage and frequency output. To counterbalance the issue with regards to the condition, the Bidirectional interlinking converter is used as an interface between power grid and energy storage to realize bidirectional energy transfer. A Pulse Width Modulator (PWM) inverter supplies currents into the utility line and a closed loop system will be introduced to allow control of the system through Proportional Integral (PI) control system. The control system parameters are calculated as required by settling time and damping ratio, and the control performances are tested via Simulink. System transient state during energy exchange period will be analysed. This report will focus on the research of bidirectional converters, the parameters realised and designing of simulation model in MATLAB, and analysis of realised parameters.